2021
DOI: 10.21203/rs.3.rs-429745/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Quality of Life, Anxiety, and Depression with Restless Leg Syndrome in the Hemodialysis Patients

Abstract: ObjectivesRestless Legs Syndrome (RLS) is commonly known to cause morbidity in patients on hemodialysis, making them prone to chronic mental health illnesses such as depression and anxiety, and also adversely impact quality of life. In this study, we examined the association of quality of life, anxiety, and depression with restless leg syndrome in the hemodialysis patients at Karachi Institute of Kidney Diseases. ResultsAbout 26.7% of the participants reported RLS among the sample size Presence of RLS was not … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Quality of Life is also influenced by social support and age of the patient (8) . Other studies have found that physical symptoms do not affect psychologically in patients undergoing hemodialysis (9) .…”
Section: Introductionmentioning
confidence: 82%
“…Quality of Life is also influenced by social support and age of the patient (8) . Other studies have found that physical symptoms do not affect psychologically in patients undergoing hemodialysis (9) .…”
Section: Introductionmentioning
confidence: 82%